From phenotypic to molecular diagnosis: Insights from a clinical immunology service focused on inborn errors of immunity in Colombia - Mónica Fernandes Pineda; Andrés F. Zea-Vera (Biomédica: revista del Instituto Nacional de Salud)
Introduction. Inborn errors of immunity include a broad spectrum of genetic diseases, in which a specific gene mutation might alter the entire emphasis and approach for an individual patient. Objective. To conduct a comprehensive analysis of the correlation between phenotypic and molecular diagnoses in patients with confirmed inborn errors of immunity at a tertiary hospital in Cali, Colombia. Materials and methods. We conducted a retrospective study in which we sequentially evaluated all available institutional medical records with a diagnosis of inborn errors of immunity. Results. In the Clinical Immunology Service of the Hospital Universitario del Valle, 517 patients were evaluated. According to the IUIS-2022 classification, 92 patients (17.35%) were definitively diagnosed with an inborn error of immunity. Of these, 38 patients underwent genetic studies. The most prevalent category was predominantly antibody deficiencies (group III) (38/92 - 41.3%). A broad spectrum of genetic defects, novel and previously reported, were described, including mutations in the following genes: ATM, BTK, ERBIN, MAB21L2, RAG2, SAVI, SH2D1A, STAT1, SYK, and TMEM173. Less frequent findings included cases of the WHIM syndrome, SYK gain-of-function, and IL-7 deficiency. Conclusions. The establishment of the Clinical Immunology Service in the Hospital Universitario del Valle has emerged as a pivotal resource, catering to individuals with limited financial means and covered by public health insurance within the southwest region of Colombia. Molecular genetics confirmatory diagnosis was achieved in 38 patients (41.3%) with inborn errors of immunity and changed the diagnosis in 24 cases (26%).